A novel approach for measuring agility in manufacturing firms. (19th September 2008) - Garbie, Ibrahim H.; Parsaei, Hamid R.; Leep, Herman R.
Manufacturing firms have great interest in developing their manufacturing systems to be more competitive in terms of flexibility and agility. Agile Manufacturing Systems (AMS) will be considered as the next industrial revolution. They are manufacturing and/or management philosophies that integrate the available technology, people, manufacturing strategies, and management systems. Although agility is the set of capabilities and competences that the manufacturing firms need to thrive and prosper in a continuously changing and unpredictable business environment, measuring the level of agility in these firms is still unexplored according to the capabilities and competences. As there are many important components (issues) to be included in embracing AMS, there are also many important questions to be asked concerning the existing firm's agility level and how to assist in achieving enhancing agility more effectively. In this paper, a novel model will be proposed to measure the agility level of the manufacturing firms based on existing technologies, level of qualifying people, manufacturing strategies, and management systems and the business process. A complete case study will be presented.